Environmental risk assessment of triclosan and ibuprofen in marine sediments using individual and sub-individual endpoints. (January 2018) - Pusceddu, F.H.; Choueri, R.B.; Pereira, C.D.S.; Cortez, F.S.; Santos, D.R.A.; Moreno, B.B.; Santos, A.R.; Rogero, J.R.; Cesar, A.
Abstract: The guidelines for the Environmental Risk Assessment (ERA) of pharmaceuticals and personal care products (PPCP) recommend the use of standard ecotoxicity assays and the assessment of endpoints at the individual level to evaluate potential effects of PPCP on biota. However, effects at the sub-individual level can also affect the ecological fitness of marine organisms chronically exposed to PPCP. The aim of the current study was to evaluate the environmental risk of two PPCP in marine sediments: triclosan (TCS) and ibuprofen (IBU), using sub-individual and developmental endpoints. The environmental levels of TCS and IBU were quantified in marine sediments from the vicinities of the Santos submarine sewage outfall (Santos Bay, São Paulo, Brazil) at 15.14 and 49.0 ng g −1, respectively. A battery (n = 3) of chronic bioassays (embryo-larval development) with a sea urchin ( Lytechinus variegatus ) and a bivalve ( Perna perna ) were performed using two exposure conditions: sediment-water interface and elutriates. Moreover, physiological stress through the Neutral Red Retention Time Assay (NRRT) was assessed in the estuarine bivalve Mytella charruana exposed to TCS and IBU spiked sediments. These compounds affected the development of L. variegatus and P. perna (75 ng g −1 for TCS and 15 ng g −1 for IBU), and caused a significant decrease in M. charruana lysosomal membrane stability at environmentally relevant concentrations (0.08 ng g −1 for TCS and 0.15 ng g −1 for IBU). Chemical and ecotoxicological data were integrated and the risk quotient estimated for TCS and IBU were higher than 1.0, indicating a high environmental risk of these compounds in sediments. These are the first data of sediment risk assessment of pharmaceuticals and personal care products of Latin America. In addition, the results suggest that the ERA based only on individual-level and standard toxicity tests may overlook other biological effects that can affect the health of marine organisms exposed to PPCP. Graphical abstract: Highlights: Triclosan and ibuprofen were quantified in order of ng.g -1 in marine sediment. Adverse effects were found in environmentally relevant concentrations. Mytella charruana is an alternative species for monitoring marine and estuarine sediments. Significant environmental risk for triclosan and ibuprofen in a tropical coastal zone. Abstract : This study presents the first data of sediment risk assessment of pharmaceuticals and personal care products in Latin America.